Genetic variation in inflammatory pathways is related to colorectal cancer survival - Coghill, Anna; Newcomb, Polly A.; Poole, Elizabeth M.; Hutter, Carolyn M.; Makar, Karen W.; Duggan, Dave; Potter, John D.; Ulrich, Cornelia (Clinical cancer research, 2011)
Purpose: Prognosis of patients with colorectal cancer (CRC) is associated with systemic inflammation, and anti-inflammatory drugs can reduce both CRC incidence and mortality. Genetic variation in proinflammatory pathways can affect an individual's CRC risk. However, few studies have investigated the prognostic importance of this genetic variation in CRC patients.Experimental Design: We investigated the association between CRC survival and genetic variation in proinflammatory pathways among patients from the Puget Sound Surveillance Epidemiology and End Results registry. Single-nucleotide polymorphisms were genotyped in five genes (PTGS-1, PTGS-2, MRP4, NFκB, and IκBKβ). Vital status was ascertained through linkage to the National Death Index. Cox proportional hazards regression was used to calculate HRs and 95% confidence intervals (CI). The false discovery rate method of Benjamini and Hochberg was applied to address multiple testing.Results: Four PTGS-1 variants were associated with CRC survival. One, G>A intron 9 (rs1213266), was associated with approximately 50% lower CRC mortality (HRAA/AG vs. GG = 0.48; 95% CI, 0.25-0.93). Three variants, including L237M, resulted in significantly elevated CRC mortality risk, with HRs ranging from approximately 1.5 to 2.0. Two variants in IκBKβ, including R526Q, were significantly associated with CRC survival. Correction for multiple testing indicated that variants in both PTGS-1 and IκBKβ are reproducibly associated with CRC survival.Conclusion: Our findings suggest that genetic variation in proinflammatory pathways may be important for CRC prognosis. This investigation represents one of the first descriptions of the relationship between inherited polymorphisms and mortality in CRC patients and provides a starting point for further research. Clin Cancer Res; 17(22); 7139-47. ©2011 AACR.
Gesehen am 04.04.2022